Talking to strangers what we should know about the people we don?t know - Gladwell, Malcolm (Blackstone, 2019)
The routine traffic stop that ends in tragedy. The spy who spends years undetected at the highest levels of the Pentagon. The false conviction of Amanda Knox. Why do we so often get other people wrong? Why is it so hard to detect a lie, read a face or judge a stranger's motives?